Association Between Caregiver Burden and Patient Recovery After Left Ventricular Assist Device Implantation: Insights From Sustaining Quality of Life of the Aged: Heart Transplant or Mechanical Support. Issue 3 (4th May 2023) - Thomas, Merrill; Spertus, John A.; Andrei, Adin-Cristian; Wu, Tingqing; Farr, Stacy L.; Warzecha, Anna; Grady, Kathleen L.
Abstract : Introduction: After left ventricular assist device (LVAD) implantation, caregivers may experience increasing burden because of new roles and responsibilities. We examined the association between caregiver burden at baseline and patient recovery after long-term LVAD implantation in patients ineligible for heart transplantation. Methods: Between October 1, 2015, and December 31, 2018, data from 60 patients with a long-term LVAD (age, 60–80 years) and caregivers through 1 postoperative year were analyzed. Caregiver burden was measured using the Oberst Caregiving Burden Scale, a validated instrument used for measuring caregiver burden. Patient recovery post–LVAD implantation was defined by change in Kansas City Cardiomyopathy Questionnaire-12 (KCCQ-12) overall summary score and rehospitalizations over 1 year. Multivariable regression models (least-squares for change in KCCQ-12 and Fine-Gray cumulative incidence for rehospitalizations) were used to assess for association with caregiver burden. Results: Patients were 69.4 ± 5.5 years old, 85% men, and 90% White. Over the first year post–LVAD implantation, there was a 32% cumulative probability of rehospitalization; 72% (43/60) of patients had an improvement of ≥5 points in KCCQ-12 scores. Caregivers were 61.2 ± 11.5 years old, 93% women, 81% White, and 85% married. Median Oberst Caregiving Burden Scale Difficulty and Time scores at baseline were 1.13 and 2.27, respectively. Higher caregiver burden was not significantly associated with hospitalizations or change in patient health-related quality of life during the first year post–LVAD implantation. Conclusions: Higher caregiver burden at baseline was not associated with patient recovery in the first year after LVAD implantation. Understanding the associations between caregiver burden and patient outcomes after LVAD implantation is important as excessive caregiver burden is a relative contraindication for LVAD implantation.